(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In order to improve the quality of education, teachers must have a combination of pedagogical skills and personal qualities to effectively teach and support the holistic development of students. This article examines the importance of pedagogical skills and personal qualities in improving the quality of education.